UJI EFEKTIVITAS ANTIBAKTERI KOMBINASI EKSTRAK KAYU MANIS (CINNAMOMUM BURMANNII) DAN DAUN KUNYIT (CURCUMA LONGA LINN.) TERHADAP BAKTERI STAPHYLOCOCCUS AUREUS - Atika Jaya Rani; Putri Yogi Selviana; Aprilia Fatma (Journal of Innovation Research and Knowledge, 2026)
Abstract: Staphylococcus aureus is one of the pathogenic bacteria found on the skin, where it exists in small numbers without causing disease; however, in larger quantities, it can lead to infections. The use of plants as traditional medicine is considered relatively effective and safe for wound management, as it rarely causes side effects and is quite affordable. The bark of cinnamon contains eugenol and cinnamaldehyde, which function as antibacterials. Additionally, turmeric leaves have bioactive compounds such as flavonoids, tannins, and phenolics that also serve as antibacterials. This study aims to analyze the phytochemical properties of a combination of cinnamon extract (Cinnamomum burmannii) and turmeric leaf extract (Curcuma longa Linn.), and to determine the antibacterial activity and inhibition zones against Staphylococcus aureus using this combination. This research is classified as a laboratory experimental study. The method used to measure antibacterial activity is the disk diffusion method. The phytochemical test results of the combination of cinnamon extract (Cinnamomum burmannii) and turmeric leaf extract (Curcuma longa Linn.) positively indicated the presence of flavonoid compounds, specifically flavanones or dihydroflavonols. The results of the antibacterial inhibition test showed that the combination of cinnamon extract and turmeric leaf extract at all concentrations of 15%, 30%, and 60% produced inhibition zones of 4.67 mm, 6.67 mm, and 12.17 mm, respectively. The combination of cinnamon extract and turmeric leaf extract effectively inhibits the growth of Staphylococcus aureus at a concentration of 60%, with an inhibition zone of 12.17 mm. Furthermore, the combination of these extracts can reduce the antibacterial effectiveness of cinnamon (Cinnamomum burmannii).